Role of specialized composition of SWI/SNF complexes in prostate cancer lineage plasticity - Cyrta, Joanna; Augspach, Anke; De Filippo, Maria Rosaria; Prandi, Davide; Thienger, Phillip; Benelli, Matteo; Cooley, Victoria; Bareja, Rohan; Wilkes, David; Chae, Sung-Suk; Cavaliere, Paola; Dephoure, Noah; et al. (Nature communications, 2020)
Advanced prostate cancer initially responds to hormonal treatment, but ultimately becomes resistant and requires more potent therapies. One mechanism of resistance observed in around 10–20% of these patients is lineage plasticity, which manifests in a partial or complete small cell or neuroendocrine prostate cancer (NEPC) phenotype. Here, we investigate the role of the mammalian SWI/SNF (mSWI/SNF) chromatin remodeling complex in NEPC. Using large patient datasets, patient-derived organoids and cancer cell lines, we identify mSWI/SNF subunits that are deregulated in NEPC and demonstrate that SMARCA4 (BRG1) overexpression is associated with aggressive disease. We also show that SWI/SNF complexes interact with different lineage-specific factors in NEPC compared to prostate adenocarcinoma. These data point to a role for mSWI/SNF complexes in therapy-related lineage plasticity, which may also be relevant for other solid tumors. The differentiation of prostate adenocarcinoma to neuroendocrine prostate cancer (CRPC-NE) is a mechanism of resistance to androgen deprivation therapy. Here the authors show that SWI/SNF chromatin-remodeling complex is deregulated in CRPC-NE and that the complex interacts with different lineage specific factors throughout prostate cancer transdifferentiation.